UNDERSTANDING NATURALLY FRACTURED RESERVOIRS - Suprajitno Munadi; Samsul Hidayat; Julikah Julikah; Oki Hendriana; Eko Susanto (Scientific Contributions Oil and Gas, 2008)
Naturally fractured reservoir differs from clastic reservoirs in the sense that the concepts of porous media which were usually applied for clastic reservoir analysis must be modified. This means that handling naturally fractured reservoir is also different compared to handling clastic reservoir. The porosity may be changed a bit bigger but the permeability is drastically changed. Also at a depth where rock layers are usually tight, naturally fractured reservoirs converts it to become a good reservoirs. Naturally fractured reservoirs can be found in some part of the Indonesian basin which may contribute a considerable additional reserves in the near future.